Digital Marketing Analysis through PPC Advertising Strategies to Improve the Competitiveness of MSMEs - Sumarno Sumarno; Fahry Reza (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
This study aims to analyze the implementation of Pay-Per-Click (PPC) Advertising through Facebook Ads in improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Pangkalpinang City and to identify the key factors influencing its effectiveness. This research was conducted in Pangkalpinang City, Bangka Belitung Islands Province using a qualitative case study approach. Data were collected through in-depth semi-structured interviews with 20 MSME actors from various sectors (culinary, crafts, fashion, services), non-participant observation of Facebook Ads Manager activities, and documentation studies. Data analysis was performed using thematic analysis techniques assisted by NVivo 12 software. The study reveals that while MSMEs in Pangkalpinang have adopted Facebook Ads, its effectiveness remains suboptimal due to three main factors: (1) imprecise targeting strategies, with 80% of MSMEs relying only on basic parameters like location (60%) and age (45%), (2) limited creative content production dominated by static images (70%), and (3) weak campaign evaluation practices, with only 35% regularly monitoring Ads Manager. This study is limited to MSMEs in Pangkalpinang City and focuses solely on the Facebook Ads platform. The research also did not quantitatively measure detailed financial aspects such as Return on Investment (ROI). This research contributes to the digital marketing literature, particularly in the context of PPC advertising for MSMEs in developing regions. Practically, it provides guidance for MSME actors, policymakers, and business development institutions in designing effective digital marketing training and mentoring programs.